Rancang Bangun Robot Sepak Bola Beroda Menggunakan Kamera Huskylens - Afridho, Jimmy; Riyanto, Agus; Satriyo, Satriyo; Ridhwan Sufandi, Muhammad; Indah Rahayu, Wiwit (entries, 2024)
A wheeled soccer robot is designed to move and kick the ball to score goals. This robot is equipped with wheels and motors for movement, a camera as its